-
If a = (√5 + 1) / (√5 - 1) and b = (√5 - 1) / ( √5 + 1) then the value of (a2 + ab + b2) / (a2 - ab + b2) is ?
-
- 3/4
- 4/3
- 3/5
- 5/3
Correct Option: B
a = [(√5 + 1) / (√5-1)] x [(√5 + 1) / (√5 + 1)]
= (√5 + 1)2 / (5 - 1)
= (5 + 1 + 2 √5) / 4
= (3 + √5) / 2
b = [(√5 - 1) / (√5 + 1)] x [(√5 - 1 ) / (√5 -1)]
= (√5 - 1 )2 / (5 - 1)
= (5 + 1 - 2√5) / 4
= (3 - √5) / 2
Now a2 + b2 = [(3 + √5)2 + (3 - √5)2] / 4
= [2 x (9 + 5 )] / 4
= 7
ab = 1
∴ (a2 + ab + b2) / (a2 - ab + b2)
= (7 + 1) / (7 - 1)
= 8/6
= 4 / 3